PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJER DENGAN BUDAYA ORGANISASI DAN PENGAWASAN PIMPINAN SEBAGAI VARIABEL MODERATING - Sa’adah, Lailatus (DINAMIKA DOTCOM, 2019)
The purpose of this research is (a) to know whether there is an influence of budget participation on managerial performance. (b) To find out whether there is an influence of organizational culture on the relationship between budgetary participation and managerial performance. (c) to find out whether there is an influence of leadership supervision on the relationship between budget participation and managerial performance. The results of this study indicate that there is an influence between budgeting participation on managerial performance on the first hypothesis, which is indicated by the value of t count of -3.777 with a significance of 0.000, which is smaller than α = 0.05. The influence of budgetary participation on employee performance shows that the higher the budgeting participation will further improve employee performance. The results of the second hypothesis indicate that there is no influence of organizational culture on the relationship between participant budgets and managerial performance. The results of the third hypothesis have no effect on leadership oversight of the relationship between budgetary participation and managerial performance. Keywords : Budget Participation, Manager Performance, Organizational Culture, Le adership Oversight.